Tanshinone IIA and Neural Stem Cell Combination Therapy Decreases Gut Inflammation and Maintains Gut Integrity in a Translational Pig Ischemic Stroke Model. (14th June 2022) - Jeon, Julie; Kaiser, Erin; Waters, Elizabeth; Yang, Xueyuan; Lourenco, Jeferson; Scheulin, Kelly; Sneed, Sydney; Shin, Soo; Kinder, Holly; Kumar, Anil; Platt, Simon; Ahn, Jeongyoun; et al.
Abstract: Objectives: Impaired gut homeostasis has been found in stroke, leading to leaky gut syndrome, increased levels of gut, brain, and systemic inflammation that further exacerbating brain damage. Tanshinone IIA (Tan IIA) and induced pluripotent stem cell derived neural stem cells (iNSCs) have been shown to decrease inflammation in the brain post-stroke resulting in reduced lesion volume and improved recovery response in rodent models. However, no group has evaluated the effect of Tan IIA and iNSCs brain treatments on intestinal changes. We evaluate the effects of Tan IIA and iNSCs delivered to the brain post-stroke on gut homeostasis in an ischemic stroke pig model. Methods: Yucatan pigs (n = 12) underwent middle cerebral artery occlusion surgery and received either PBS (CON) or Tan IIA loaded PLGA nanoparticle (Tan IIA-NPs) and iNSCs treatment (TRT). PBS or Tan IIA-NPs were administered intracisternally at 1 hour post-stroke and PBS or iNSCs were transplanted into the perilesional region at 5 days post-stroke. Changes in fecal total SCFAs level were analyzed up to 12 weeks (wk) post-treatment (PT) and jejunum scrapings were collected at 12 wk PT for analysis. Results: TRT had higher levels of total SCFAs than CON throughout the study period. Protein levels of jejunal TNF-α, TNFR1, and phosphorylation of Ikbα at 12 wk PT were lower in TRT compared to CON, suggesting that the treatment in brain decreased gut inflammation. The expression of jejunal Occludin, Claudin1, and ZO-1 was higher in TRT compared to CON. Moreover, protein levels of TNF-α and phosphorylation of Ikbα were negatively correlated with fecal total SCFAs levels at early stages of treatment (1–4 wk PT). Interestingly, total SCFA level at early treatment stages (up to 4 wk PT) was inversely related to hemorrhage volume measured by magnetic resonance imaging 1 day post-stroke, indicating a potential link between stroke severity and gut homeostasis. Conclusions: The findings of the study indicate that local post-stroke brain treatment with Tan IIA and iNSCs decreases inflammation and membrane permeability through dynamic interplay with SCFAs in the gut. This study suggests further research on inflammation and SCFAs as key regulatory components and potential therapeutic targets that can modulate the gut brain axis to enhance stroke recovery in patients. Funding Sources: This work was supported by the National Institutes of Health.